1994
DOI: 10.1248/bpb.17.859
|View full text |Cite
|
Sign up to set email alerts
|

A Glucan Having Reticuloendothelial System-Potentiating and Anti-complementary Activities from the Tuber of Pinellia ternata.

Abstract: A glucan, called pinellian G, was isolated from the tuber of Pinellia ternata BREIT. It was homogenous on electrophoresis and gel chromatography, and its molecular mass was estimated to be 1.5 x 10(4). It is composed solely of D-glucose, in addition to a few O-acetyl groups. Methylation analysis, nuclear magnetic resonance and enzymic degradation studies indicated that it is a branched glucan mainly composed of alpha-1,4-linked D-glucopyranose residues with partially alpha-1,3-linked units and 4,6-branching po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…While many basic studies on the pharmacologic effects of Amomi Semen have been reported (20,23,24), the immunologic effects for DCs are not known. Pinelliae Tuber is the tuber of Pinellia ternata (Family: Araceae), and its acidic polysaccharides possess anti-complement and reticuloendothelial system activation activities (22). Recent studies of the anti-influenza virus activity of Sho-sei-ryu-to (Chinese medicine formulation) and pinellic acid (9S,13S-trihydroxy-10E-octadecenoic acid), isolated from Pinelliae Tuber, indicate that these herbal medicines have adjuvant effects in influenza vaccination (17).…”
Section: Discussionmentioning
confidence: 99%
“…While many basic studies on the pharmacologic effects of Amomi Semen have been reported (20,23,24), the immunologic effects for DCs are not known. Pinelliae Tuber is the tuber of Pinellia ternata (Family: Araceae), and its acidic polysaccharides possess anti-complement and reticuloendothelial system activation activities (22). Recent studies of the anti-influenza virus activity of Sho-sei-ryu-to (Chinese medicine formulation) and pinellic acid (9S,13S-trihydroxy-10E-octadecenoic acid), isolated from Pinelliae Tuber, indicate that these herbal medicines have adjuvant effects in influenza vaccination (17).…”
Section: Discussionmentioning
confidence: 99%
“…Its Rhizoma (PR) has been used in Traditional Chinese Medicines (TCMs) for its antiemetic, antitussive, anti-tumor, antimicrobial, anti-obesity, anticonvulsant activities and other therapeutic efficacies [1][2][3][4][5][6]. Studies have shown that the main constituents of PR are proteins, alkaloids, polysaccharides and organic acids [7][8][9][10]. Recently, it has been reported that an increasing number of polysaccharides from natural sources have excellent antioxidant activities [11].…”
Section: Introductionmentioning
confidence: 99%
“…Modern phytochemical studies showed that the content of starch in PR is as high as 75% [10]. In addition, alkaloids, essential oils, amino acids, organic acids, and proteins are the chemical components of PR [7,11,12,13]. Unfortunately, the specific purified compounds derived from the herb were still not obtained.…”
Section: Introductionmentioning
confidence: 99%